ANALYTICAL METHOD DEVELOPMENT AND VALIDATION OF AMOXICILLIN AND CLOXACILLIN IN API AND ITS DOSAGE FORM BY RP-HPLC - Sony Chaudhary, Obed Singh, Dr. Shivanand Patil (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
A simple, accurate, precise, sensitive and stability indicating reverse phase high performance liquid chromatography method has been developed for simultaneous determination of Amoxicillin and Cloxacillin sodium in bulk and in combined capsule dosage form. Chromatographic separation was performed on C18 column, with mobile phase consist of water, acetonitrile, and methanol in the ratio of 70:20:10 (v/v/v), at flow rate 1.4 ml/min. Quantification of both drugs was achieved at UV detector at 238.8 nm. The retention time of Amoxicillin and Cloxacillin sodium was found to be 8.240 and 14.036 minute respectively with run time 20 minutes. Amoxicillin and Cloxacillin followed the linearity in concentration range 20-100 µg/ml for both with correlation coefficient (r2) values 0.998 for Amoxicillin and 0.998 for Cloxacillin sodium. The proposed method was validated according to ICH guidelines in terms of linearity, accuracy, precision, LOD and LOQ. Percentage assay was found to be 98.92 % and 99.61 % for Amoxicillin and Cloxacillin respectively. In precision % RSD was found to be < 2% for both. The percentage recovery was found in range 99.18%-99.42%. The LOD and LOQ values were within limit. The degradation studies carried under condition of acid, base, neutral, oxidative, photolysis, thermal degradation and no attempt was made to identify the degradation product.